Hubungan Berpikir Kritis dengan Kemampuan Pemecahan Masalah pada Siswa Kelas VIII SMP Negeri 2 Serui - Handry Alfred Fonataba; Nancy Susianna; Nerru Pranuta Murnaka (JIMAD: Jurnal Ilmiah Mutiara Pendidikan, 2026)
The paradigm shift in science education necessitates the development of critical thinking skills as a foundation for improving students’ problem-solving abilities; however, empirical conditions indicate that both competencies remain low and have not been optimally developed. This study aims to examine the relationship between critical thinking skills and problem-solving abilities among eighth-grade students of SMP Negeri 2 Serui and to determine the degree of their empirical association. The study employed a quantitative approach with a correlational design, utilizing essay-based test instruments analyzed through simple linear regression. The findings reveal that students’ critical thinking and problem-solving abilities are in the low to moderate categories, with mean scores of 14.56 and 28.72, respectively. The linearity test indicates a significant relationship, while regression analysis produces the equation Y = 21.682 + 0.484X with a significance value of 0.009. The correlation coefficient of 0.487 indicates a moderate positive relationship, and the coefficient of determination of 23.7% shows that critical thinking contributes to problem-solving ability. The results confirm that improvements in critical thinking skills directly influence the enhancement of students’ problem-solving abilities, although other factors also contribute. The novelty of this study lies in the presentation of a quantitative relationship model that remains significant despite non-normally distributed data, as well as in establishing critical thinking as a significant yet partial predictor of problem-solving, thereby providing a foundation for developing more structured, contextual, and higher-order thinking-based instructional strategies.